2002
DOI: 10.1063/1.1519100
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN single-quantum-well light-emitting diodes with emission at 285 nm

Abstract: We report on AlGaN single-quantum-well light-emitting diodes (LEDs) on sapphire with peak emission at 285 nm. A study is presented to identify the key material parameters controlling the device quantum efficiency. At room temperature, for a 200 μm×200 μm square geometry mesa type device, we obtain a power as high as 0.25 mW for 650 mA pulsed pumping. The LEDs show significantly higher output powers at temperatures below 100 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…For the 285 nm emission, we previously reported room-temperature power as high as 0.25 mW for a pulsed pump current of 650 mA. 9 These studies 8,9 also concluded that the emission band at 330 nm resulted from a recombination of the electrons via deep neutral acceptor levels in the p-AlGaN layer of our device structure. The data suggested that the weak carrier confinement not only results in a long-wavelength emission ͑at 330 nm͒, but it also reduces the 285 nm emitted powers.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…For the 285 nm emission, we previously reported room-temperature power as high as 0.25 mW for a pulsed pump current of 650 mA. 9 These studies 8,9 also concluded that the emission band at 330 nm resulted from a recombination of the electrons via deep neutral acceptor levels in the p-AlGaN layer of our device structure. The data suggested that the weak carrier confinement not only results in a long-wavelength emission ͑at 330 nm͒, but it also reduces the 285 nm emitted powers.…”
mentioning
confidence: 85%
“…The data suggested that the weak carrier confinement not only results in a long-wavelength emission ͑at 330 nm͒, but it also reduces the 285 nm emitted powers. 9 Additionally, the number of nonradiative defects is a key factor that controls the quantum efficiency of LED devices. 3 The number of nonradiative defects is itself a strong function of the buffer and the active layers material quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The progress in improving efficiency of light emitting diodes as well as in achieving an increasingly shorter emission wavelength continues rapidly. 2,3 Introduction of indium and/or aluminum into GaN plays a key role in strain and band engineering of nitrides. 4 Indium is demonstrated to smooth the chaotic band-tail potential induced by partial disorder in the nitride alloys due to composition fluctuations 5 and, thus, facilitates hopping of localized excitons at low temperatures.…”
mentioning
confidence: 99%
“…In addition, the spectral resolution can be improved by introduction of narrow-band interference filters, since LEDs with a high enough spectral power density of the emission are readily available. Another improvement of this technique is expected with further development of UV LEDs that allow one simultaneously to excite fluorescence of many organic compounds (a 285 nm LED has been already reported 14,15 .…”
Section: Resultsmentioning
confidence: 99%